MEMBRAN SELULOSA SEBAGAI MEDIA ULTRAFILTRASI UNTUK MENURUNKAN KADAR BESI DALAM AIR - - Faridah; - Efiana; - Saifuddin; - Jamaluddin (Politeknik Negeri Lhokseumawe, 2014)
The contain of iron ions in water causes the water color become brownish yellow and water become also smelly. There are any ways that can be done to eliminate the iron ions in the water, one of them is by using membrane as a filter medium. This study offered cellulose membranes which is able to reduce iron levels in water by using various types of cellulose membranes, such as celluose membrane I derived from derived from sugar juice, cellulose membrane II from coconut water and cellulose membrane III which is derived from the combaining of sugar juice and medium coconut water. After the cellulose membranes were produced, it then was applied to reduce iron ions in water. The samples were taken from water wells in Geudong area which have the iron inons around 0,203 ppm and water drilled wells in Politeknik Negeri Lhokseumawe area which contains the iron ions around 0.184 ppm. After using the cellulose membrane as ultrafiltration for both of samples, it was found that the iron ions contain in water had reduced. The best cellulose membrane to be used was the cellulose membrane II which is derived from coconut water. The effecency of iron reduction was founded in artificial (sampel III) sampel around 91,73%, following sampel I from Politeknik Negeri Lhokseumawe around 68,75% and sampel II from Geudong area around 59,46%. The results showed that the membrane of coconut water is able to reduce iron in the water with higher efficiency than other membranes